Impaired B-cell reconstitution in children after chemotherapy for standard or medium risk acute precursor B-lymphoblastic leukemia. Issue 4 (April 2014) - Wiegering, Verena; Frank, Jana; Freudenberg, Sandra; Morbach, Henner; Schlegel, Paul G.; Eyrich, Matthias; Winkler, Beate
Abstract Chemotherapy for childhood acute lymphoblastic leukemia (ALL) is a highly effective treatment, but at the same time causes significant suppression of the patient's immunity. Immune reconstitution was studied in a homogeneous cohort of 48 children with standard or medium risk ALL treated according to the ALL-Berlin–Frankfurt–Münster (BFM) protocol. Whereas the T-cell compartment was only moderately affected and recovered to normal levels quickly after treatment cessation, B-cells were significantly reduced during and after therapy. In particular, the naive B-cell compartment declined. Even 5 years after the end of therapy, B-cell distribution was disturbed and patients showed an ongoing reconstitution. Thus, even standard regimens for chemotherapy cause severe B-cell depletion that resolves only gradually.